Research Progress in Heterologous Expression, Fermentation and Application of Microbial Transglutaminase - YAN Wenhui, SUN Xinjie, XI Xiangheng, WANG Chenying, REN Xidong (Shipin Kexue, 2023)
Transglutaminase (TG) is a widely used enzyme with excellent protein cross-linking capacity. TG is commonly found in plants, animals and microorganisms, and microbial TG (mTG) is widely used in industrial production and application because of its good enzymatic properties. This paper describes the physicochemical properties and activation mechanism of mTG, and summarizes recent progress in mTG production by wild and different genetically engineered strains. Meanwhile, the application and potential of mTG in various industrial fields are reviewed. This review is expected to provide a reference and new ideas for research on the potential of mTG for industrial production and application.